PERAN MANAJEMEN KELAS DALAM MEWUJUDKAN PEMBELAJARAN YANG KREATIF - Dwiyana, Sinta; Ade Akhmad Saputra (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
This research aims to analyze the role of classroom management in creating creative learning at SDN Pemulutan Barat 3 Kamal Village. Using a qualitative-based descriptive approach, this research involves students and teachers as subjects, and data collection through observation, interviews, direct communication and documentation. The research results show that classroom management plays an important role in creating a conducive learning environment, with a focus on positive interactions between teachers and students. Teachers at this school have implemented various classroom management techniques to increase student participation and create a pleasant learning atmosphere. Creative learning is carried out through various methods, such as group discussions and project assignments, which aim to encourage student creativity. However, limited facilities and time often become obstacles in implementing more interactive and innovative learning. In addition, the application of learning styles is adjusted to student characteristics, although technological limitations are the main obstacle in integrating more modern learning media.